Cost-Utility Analysis of Molecular Testing for Tuberculosis Diagnosis in Suspected Pulmonary Tuberculosis in Thailand - Chitpim N; Jittikoon J; Udomsinprasert W; Mahasirimongkol S; Chaikledkaew U (Dove Medical Press, 2022)
Natthakan Chitpim,1 Jiraphun Jittikoon,2 Wanvisa Udomsinprasert,2 Surakameth Mahasirimongkol,3 Usa Chaikledkaew4,5 1Social, Economic and Administrative Pharmacy (SEAP) Graduate Program, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 2Department of Biochemistry, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 3Medical Genetics Center, Medical Life Sciences Institute, Department of Medical Sciences, Ministry of Public Health, Bangkok, Thailand; 4Social Administrative Pharmacy Division, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 5Mahidol University Health Technology Assessment (MUHTA) Graduate Program, Mahidol University, Bangkok, ThailandCorrespondence: Usa ChaikledkaewSocial and Administrative Pharmacy Division, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, 447 Sri-Ayudhaya Road, Rajathevi, Bangkok, 10400, Thailand, Tel +66 2-644-8679 ext 5317, Fax +66 2-644-8694, Email usa.chi@mahidol.ac.thPurpose: Given the lack of economic evaluation study of molecular testing in Thailand, this study aimed to evaluate the cost-utility of molecular testing algorithms including Xpert MTB/RIF and the loop-mediated isothermal amplification (TB-LAMP) in the general population suspected of having pulmonary TB based on a societal perspective.Methods: A hybrid decision tree Markov model using a 1-month cycle length was used to evaluate costs and outcomes of five TB diagnostic algorithms: 1) sputum smear microscopy (SSM) with culture and drug susceptibility testing (DST), 2) Xpert MTB/RIF add-on, 3) Xpert MTB/RIF initial, 4) TB-LAMP add-on, and 5) TB-LAMP initial during a lifetime period. All costs were calculated in 2021 Baht, and results were presented as an incremental cost-effectiveness ratio (ICER) for molecular testing compared with SSM with culture. One-way sensitivity and probability analyses were used to evaluate uncertainty input parameters.Results: TB-LAMP was less expensive overall (6565 Baht) than Xpert MTB/RIF (7010 Baht) and SSM with culture (6845 Baht). Molecular testing was projected to improve quality adjusted life year (QALY) by 0.53 to 0.94 years. In comparison to SSM with culture and DST, providing an initial TB-LAMP test was the most preferred choice. Xpert MTB/RIF Initial had the lowest ICER (197 Baht per QALY gained), followed by TB-LAMP Add-on (993 Baht per QALY gained) and Xpert MTB/RIF Add-on (3940 Baht per QALY gained). One-way sensitivity analysis uncovered that sensitivity of TB-LAMP was greater than that of other parameters.Conclusion: Providing molecular testing including Xpert MTB/RIF and TB-LAMP as either initial or add-on test for TB diagnosis was more cost-effective than SSM with culture and DST in the general population with suspected pulmonary TB in Thailand. Our study could provide useful evidence to policymakers advocating for inclusion of molecular testing in the universal health coverage benefit package in Thailand.Keywords: molecular testing, economic evaluation, diagnosis tuberculosis, Xpert MTB/RIF, TB-LAMP